Ozone therapy in orofacial harmonization (Research, Society and Development, 2023)
The ozone molecule (O3) was discovered in the mid-nineteenth century by the German chemist Christian Friederich Schönbein, and had wide application in the field of health, mainly due to its antimicrobial characteristics and others associated with cell multiplication. During the last 150 years, O3 has been widely applied to treat wound infections, in addition to treating more than 100 different pathologies. This narrative review of the literature aims to provide a document to guide the specialist regarding the possible indications of ozone therapy as an adjunct to orofacial harmonization (HOF). One of the most used forms of O3 in HOF is in its form of oil, gas or intradermal application. The oil has also been successfully used in cosmetic formulations, producing innovative products with more attractive properties, as it guarantees a natural aroma and facilitates the penetration of active ingredients into the deepest parts of the skin, increasing the hydration effect and even more, protecting cosmetics from microbial contamination. It was concluded with this research that, despite the recent use and understanding of the mechanisms of the ozone therapy technique as a complement in the treatment of various pathological or aesthetic conditions that are presented in the clinic of the specialist in HOF, the in-depth knowledge of the dental surgeon must be a condition necessary for the indication of the technique, form of application and understanding of the contraindications to avoid iatrogenic events, and finally, to improve the patient's quality of life.